Case report: Xanthogranulomatous pyelonephritis masquerading as cystic renal cell carcinoma. Issue 2 (2nd April 2020) - Mohaghegh P, SM; Wong, RS; Rahimi, M; Shih, F; Bansal, R
ABSTRACT: Background: Xanthogranulomatous pyelonephritis (XGP) is a rare chronic bacterial inflammation of the renal parenchyma and is often a diagnostic dilemma. Case Presentation: We present a challenging case of a patient with XGP. Initially thought to have had renal cell cancer she was treated accordingly with a partial nephrectomy. However, on the final pathology, she was found to have XGP and required further antibiotic therapy and referral to the infectious disease service. Discussion: Management of XGP and diagnostic pitfalls are discussed. Conclusion: XGP is a diagnostic and therapeutic dilemma. Partial Nephrectomy may be appropriate in management of XGP in select cases.